Paisajes y prácticas sociales en las Selvas meridionales de la provincia de Tucumán (1° milenio D.C.) - Miguez, Gabriel Eduardo (2015)
The prehispanic archaeology of the lowlands of northwest Argentina has had less development in comparison to that of other sub-areas (e.g. valleys, Puna). In this context, the southern piedmont of Tucumán province has been one of the least investigated sections of the lowlands. We suggest that among other reasons, this is the result of on the one hand the limitations of the theoretical and methodological perspectives followed by previous studies (where the piedmont was seen as a peripheral area to highlands ?centers?) and, on the other the traditional perception of poor preservation in this kind of environment. Recent investigations focused on the study of archaeological landscapes involved the application of a field methodology that has enabled us to register sites and contexts that allow a deeper approach concerning the communities that inhabited these rain-forests during the first 1200 years AD. We summarize the evidence of two sites (Santa Rosa and Yánimas 1) to interpret landscapes and social practices in the area, hoping to demonstrate that another perspective about piedmont archaeology is possible.